Polarization scattering-based detection of lubricating materials - Liu, Xin; Jian, Junxin; Huang, Xiaolu; Li, Huilong; Tian, Yuan; Ma, Weizhi; Zhao, Xiaolong; Liu, Zunnian; Sun, Jiayi; Zhang, Xiushuo; Wang, Yong; Zhu, Xiaomei (Frontiers in Materials, 2025)
Friction, wear, and corrosion are common phenomena in both industrial and daily life, significantly impacting the performance, lifespan, and energy efficiency of equipment. To mitigate these adverse effects, current research primarily focuses on the development of novel materials, surface modification techniques, and lubricating coatings. Accurate detection and evaluation are crucial for understanding material behavior under varying conditions, which not only aids in optimizing material design but also enables timely identification and repair of potential issues, thereby extending equipment lifespan and enhancing reliability. Addressing the limitations of existing detection methods in real-time monitoring and micro-defect detection, this study proposes a polarization-based detection method to more accurately assess and optimize the friction, wear, and corrosion properties of materials. This method leverages the polarization characteristics of light to investigate the optical properties and microstructures of materials, offering advantages such as high data dimensionality, sensitivity to microstructural changes, and compatibility with existing optical techniques. We constructed a polarization detection system and employed data analysis methods, such as linear discriminant analysis, to study various samples. By using this system, we extracted specific parameters sensitive to different characteristic variables, enabling us to more accurately characterize the lubrication performance of materials and providing valuable insights for material optimization. The proposed polarization-based detection method offers a new approach for evaluating the friction, wear, and corrosion properties of materials, demonstrating potential for real-time monitoring and micro-defect detection, and is expected to enhance equipment lifespan and reliability.